2022
DOI: 10.1007/s11102-022-01261-9
|View full text |Cite
|
Sign up to set email alerts
|

Hypercoagulability in Cushing’s syndrome: incidence, pathogenesis and need for thromboprophylaxis protocols

Abstract: Cushing's syndrome (CS) is associated with a hypercoagulable state resulting in an increased risk on venous thromboembolism (VTE). In patients with untreated active CS VTE incidence is up to 18-fold higher compared to the general population, whereas after pituitary and adrenal surgery a postoperative VTE risk between 2.6 and 5.6% has been reported. Interestingly, after surgery the VTE risk is not only increased in the first week but also during several months postoperatively. The hypercoagulable state in CS is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Cushing's syndrome is associated with hypercoagulable state, leading to an increased risk of venous thromboembolism (VTE) (62). Among untreated CS patients, the incidence of VTE was 18 times higher than that of the general population, and the risk of VTE decreased significantly after surgical resection of adrenal tumors (63). The hypercoagulable state of CS is not fully understood, and some studies suggest that it is caused by the imbalance between activity of procoagulant and anticoagulant pathways (62).…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Cushing's syndrome is associated with hypercoagulable state, leading to an increased risk of venous thromboembolism (VTE) (62). Among untreated CS patients, the incidence of VTE was 18 times higher than that of the general population, and the risk of VTE decreased significantly after surgical resection of adrenal tumors (63). The hypercoagulable state of CS is not fully understood, and some studies suggest that it is caused by the imbalance between activity of procoagulant and anticoagulant pathways (62).…”
Section: Treatmentmentioning
confidence: 99%
“…The hypercoagulable state of CS is not fully understood, and some studies suggest that it is caused by the imbalance between activity of procoagulant and anticoagulant pathways (62). Functional analysis showed that the partially activated thromboplastin time was shortened and the thrombolysis time was increased in patients with CS (63,64). This may aggravate the coagulation dysfunction in patients with OAPS, affect uterine and placental circulation, and lead to a series of adverse pregnancy outcomes (11,16,63,64).…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that endogenous hypercortisolism is associated with increased morbidity and mortality ( 4 , 5 , 6 ). This increased risk is mainly driven by cardiovascular events, including venous thromboembolic events (VTEs) such as pulmonary embolism (PE) and deep vein thrombosis (DVT).…”
Section: Introductionmentioning
confidence: 99%
“…Several complications of CS have recently been more readily recognized, requiring new personalized treatment and prohylaxis protocols. These include hypercoagulability [15] and increased risk of venous thromboembolism (up to 18 times higher than normal population), cardiovascular disease [16] as the main cause of mortality and associated multifactorial bone disease [17]. In some patients, although growth hormone deficiency [18] may improve after surgical resection, low IGF-1 has been linked to persistent myopathy.…”
mentioning
confidence: 99%